STUDI LITERATURE KESULITAN SISWA SMP/MTs DIPONEGORO WULUHAN DALAM PEMBELAJARAN MATA PELAJARAN BAHASA INGGRIS - Lamatsil Imroatus Sholehah (ScienceEdu: Jurnal Pendidikan IPA, 2019)
Abstract Learning difficulty is a condition where students experience learning disruptions as they should, both from internal and external factors. This results in students not being able to develop according to their capacity. From this research can be put forward the formulation of the problem, namely, the types of learning difficulties experienced by junior high school / junior high school students in North Sumatra, what factors that make students difficult to learn in English, and how can efforts solve the problem of student learning difficulties. The purpose of this study was to determine the types of difficulties in understanding completing the material in English subjects, the factors that influence students in understanding completing the material in English subjects and problem solving efforts. The method used in this study is to use qualitative methods. Data collection techniques used were literature studies and interviews with each student were different classes. The results of this study are that there are still some students who still have difficulty in understanding completing the material in English subjects from the aspects of listening, reading, structure, and writing, and which are the factors causing students to experience learning difficulties, namely from cognitive factors (ability to memorize , the ability to master the material and the wrong learning habits, and what efforts will be used by educators using teaching repairs. Keywords: learning difficulties, students, English.